Radionuclídeos naturais em minas subterrâneas brasileiras - Talita de Oliveira Santos (2015)
Rock, soil and water contain 238U and 232Th and their decay products. The distribution of these radionuclides differs in terms of activity concentration depending on the mineral type and origin. All ore processing releases long and short half-life radionuclides, mainly radon and its progeny. It is important to monitor this gas and its decay products in underground mines in order to assess the radiological hazards of the exposed workers. On this concern, the present work outlines the characterization of brazilian underground mines with relation to natural radionuclides, specially radon and its progeny. The radon concentration was measured by using E-PERM Electrets Ion Chamber (Radelec), AlphaGUARD (Saphymo GmbH) and CR-39 (Landauer) track etchdetectors. The radon progeny was determined by using DOSEman detector. The equilibrium state between radon and its progeny was calculated. Based on these data, the total effective dose for miners was estimated. Moreover, the contribution from the main sources to the radon level inside mines was evaluated. For this, the following detectors were used: measurements of radon concentrations in soil gas were carried out by using AlphaGUARD detector; 226Ra (214Bi), 232Th e 40K specific activity in ore and soil samples were determined by using gamma-ray spectrometry HPGe detector (Canberra); and radon concentration in groundwater samples was performed by using RAD7 (Durridge Inc.). The radon concentration ranged from 113 to 8171 Bq.m-3 and the Equilibrium Equivalent Concentration varied from 76 to 1174 Bq.m-3. The equilibrium factor mean value was 0.4 (0.2 0.7). The workers estimated total effective dose ranged from 1 to 22 mSv.a-1 (mean 10 mSv.a-1). Therefore, results show the importance to assess continually and permanently the radon and its progeny behavior and the need to adopt safety measurements against natural radiation in underground mines environment.